Mucocutaneous Manifestations of Behçet's Disease - Nakamura, Koichiro; Tsunemi, Yuichiro; Kaneko, Fumio; Alpsoy, Erkan (Frontiers in Medicine, 2021)
Behçet's disease (BD) is a chronic, relapsing, systemic inflammatory disease with clinical features showing mucocutaneous lesions involving the ocular, articular, and further miscellaneous organs. Mucocutaneous manifestations, one of the most characteristic signs of BD, have been most commonly observed upon onset or at any disease stage and are exceptionally important in its diagnosis. Given the lack of specific diagnostic laboratory tests for BD, diagnosis has been based on clinical findings. All diagnostic criteria published have thus far relied heavily on mucocutaneous manifestations, particularly oral ulcers (OU), genital ulcers (GU), cutaneous lesions, and pathergy test positivity. Worldwide, OU, GU, cutaneous lesions, and ocular and articular manifestations have been the most common symptoms, with erythema nodosum (EN)-like lesions and papulopustular lesions being the most prevalent cutaneous manifestations. While majority of the patients worldwide have reported OU as the most frequent symptom upon disease onset, GU, and EN-like lesions have also been identified upon onset. Considering that mucocutaneous symptoms precede severe organ involvement in most patients, familiarity with such symptoms is imperative for early diagnosis and prevention of potentially serious organ involvement through appropriate management.